2012
DOI: 10.4314/rj.v25i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Land Tenure Security in Informal Settlements of Kigali City. Case study in Muhima Sector

Abstract: Rapid urbanization of Kigali City is a direct consequence of increasing development of informal settlements in the city. This research sought to identify

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Empirical studies conducted within the urban areas of Nigeria and other sub-Saharan African countries have indicated that public institutions are not performing sufficiently. The studies of Twarabamenye and Nyandwi (2012) in Butare Town in Tumba section of Rwanda and Bizimana, Mugirameza, Twarabamenye, and Mukeshimana (2012) in Kigali all provides evidence of unrestrained informal land market activities. This accounts for 68.7% of land access compared to government's 7.7%, making local sales agreement the predominant evidence of proof of ownership.…”
Section: Inadequacies Of Public Institutions and Informal Land Marketsmentioning
confidence: 99%
“…Empirical studies conducted within the urban areas of Nigeria and other sub-Saharan African countries have indicated that public institutions are not performing sufficiently. The studies of Twarabamenye and Nyandwi (2012) in Butare Town in Tumba section of Rwanda and Bizimana, Mugirameza, Twarabamenye, and Mukeshimana (2012) in Kigali all provides evidence of unrestrained informal land market activities. This accounts for 68.7% of land access compared to government's 7.7%, making local sales agreement the predominant evidence of proof of ownership.…”
Section: Inadequacies Of Public Institutions and Informal Land Marketsmentioning
confidence: 99%
“…The inadequate supply and then-dominant system of land distribution were not in a position to meet the needs of a dynamically growing number of urban residents. The population flowing in was forced to purchase land belonging to the state prior to gaining a right to use or right of ownership [78].…”
Section: Spatial Planning and Urban Agriculture Managementmentioning
confidence: 99%
“…Informal settlement neighborhoods in Kigali City have no open sewers, an average density of 190 persons per hectare, and low crime rates (Benken, 2017). Regarding with living conditions in informal settlements, the major concern is the lack of land security (Bizimana, 2012). The main of this study was to analyze the stakeholder's engagement and performance of urban informal settlement upgrading project in Kigali.…”
Section: Introductionmentioning
confidence: 99%